This Gospel shall be preached essays on the Australian contribution to world mission - Hutchinson, Mark Peter, 1958-; Treloar, Geoffrey Robert, 1951- (Sydney NSW The Centre for the Study of Australian Christianity, Robert Menzies College, Macquarie University, 1998)
Includes bibliographical references and index.
Ch 15 : Ken Newton: The contribution of the Brethren to Australian missionary thought and practice.
Keywords: Christianity -- Australia; Christianity -- missions; Australia -- international relations